1997
DOI: 10.2331/fishsci.63.963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Essential Amino Acid Requirements with A/E Ratio among Fish Species (Review Paper)

Abstract: So far, the dietary requirements of the ten amino acids arginine, histidine, isoleucine, leucine, ly sine, methionine, phenylalanine, threonine, tryptophan and valine have been proved in fish and the quantitative requirements have been determined in several fishes. However, each essential amino acid re quirement determined by different laboratories does not correspond with each other, not only among species but also even within species, because of the differences of experimental conditions. Therefore, some res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 18 publications
1
99
0
2
Order By: Relevance
“…According to Jobling (1994), nutritional requirements of fish of the same age reared in the same environment and under the same feeding regime are influenced by their size and degree of sex maturity. Akiyama et al (1997) reported that variations in amino acid requirements of different species possibly reflect true differences between phylogenetically distinct families or species. In view of differences found in growth rates between individual groups (Table 1), unequal intakes of plant and animal protein (especially essential amino acids) may have ensued as a result of trophic competition.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jobling (1994), nutritional requirements of fish of the same age reared in the same environment and under the same feeding regime are influenced by their size and degree of sex maturity. Akiyama et al (1997) reported that variations in amino acid requirements of different species possibly reflect true differences between phylogenetically distinct families or species. In view of differences found in growth rates between individual groups (Table 1), unequal intakes of plant and animal protein (especially essential amino acids) may have ensued as a result of trophic competition.…”
Section: Discussionmentioning
confidence: 99%
“…While the individual, essential amino acid requirements of zebrafish have not been systematically tested, assuming similar requirements to other fish, 20,23 it may not be surprising that the wheat-fed fish exhibited the lowest growth, provided the known limitations of lysine in wheat. 23,[36][37][38] Previous research with soy protein also might suggest that limitation of essential, sulfur-containing amino acids (methionine and cysteine) might be expected to limit growth outcomes, 28,39,40 but the fish in this study responded well with similar growth outcomes to the MIX control diet.…”
Section: Figmentioning
confidence: 99%
“…10,11 Although it is commonly ascribed that caloric consumption is the main determinant of the growth, health, and longevity outcomes, it also appears that dietary composition (particularly the protein amount, source, and individual amino acids-e.g., methionine) may directly/indirectly contribute to health and longevity outcomes. requirements may be predicted based on other nutrition studies using teleost models, [20][21][22][23] few nutrient requirement studies have been formally presented in the research literature for zebrafish. 3,24,25 Nevertheless, although zebrafish nutrition and obesity research is still developing compared with rodent models, 26 the information reported from decades of rodent nutrition research may be used to rapidly test dietary compositions for a variety of growth and eventual health-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, o fornecimento adequado de lisina na dieta permite o correto balanceamento dos demais aminoácidos essenciais, em decorrência de sua alta correlação entre o perfil de aminoácidos da carcaça e o exigido pelo peixe (Akiyama et al, 1997), e possibilita a redução do nível proteico a partir da utilização de alimentos cujos aminoácidos sejam de alto valor biológico.…”
Section: Resultsunclassified